Implementasi Metodologi Prototype dalam Pengembangan Sistem Manajemen Kehadiran Pegawai Perusahaan Berbasis Web - Hartanto Situmorang; Muhammad Ihsan Zul (Sekawan Institut, 2024)
Employee Attendance data has an important function in evaluating productivity and work discipline. The current management of employee attendance data at the CV Baja Diva Manufaktur company requires the administrator to check attendance data from the Excel file generated by the fingerprint machine. This management is done by checking the attendance data of each employee individually. In addition, administrative processes related to permits, warning letters, and overtime are also carried out manually, which requires employees to report directly to the office. This process is time-consuming and prone to data input errors. Therefore, this research aims to develop a system that is more efficient and flexible in managing employee attendance data. The research also revealed that most employees have little to no experience in information technology-based management systems. The methodology applied in this research is the prototype methodology, which was chosen because it can provide a better understanding of user needs and perspectives through continuous feedback during the development process. The implementation of the prototype methodology involved four iterations, where each iteration included the stages of listening to user feedback and complaints, building and refining the prototype, and testing and evaluating the prototype with users. The results of the prototype were then implemented using the CodeIgniter framework. Feedback from users showed that the prototype effectively met users' needs and significantly improved the efficiency of attendance management. The usability testing results using questionnaires from 20 users showed an average satisfaction rate of 95.85%, indicating that this system can be applied in various organizations.